The politics of Islamic law - Hussin, Iza R. (Chicago)
viii, 351 sayfa
Keywords: “In The Politics of Islamic Law, Iza Hussin compares India, Malaya, and Egypt during the British colonial period in order to trace the making and transformation of the contemporary category of ‘Islamic law.’ She demonstrates that not only is Islamic law not the shari’ah, its present institutional forms, substantive content, symbolic vocabulary, and relationship to state and society -in short, its politics- are built upon foundations laid during the colonial encounter. Drawing on extensive archival work in English, Arabic, and Malay -from court records to colonial and local papers to private letters and visual material- Hussin offers a view of politics in the colonial period as an iterative series of negotiations between local and colonial powers in multiple locations. She shows how this resulted in a paradox, centralizing Islamic law at the same time that it limited its reach to family and ritual matters, and produced a transformation in the Muslim state, providing the frame within which Islam is articulated today, setting the agenda for ongoing legislation and policy, and defining the limits of change. Combining a genealogy of law with a political analysis of its institutional dynamics, this book offers an up-close look at the ways in which global transformations are realized at the local level“ --